External debt and economic growth in Sub-Saharan Africa: Does governance matter? - Manasseh, Charles O.; Abada, Felicia C.; Okiche, Ebelechukwu L.; Okanya, Ogochukwu; Nwakoby, Ifeoma C.; Offu, Peter; Ogbuagu, Anuli R.; Okafor, Chiedozie O.; Obidike, Paul C.; Nwonye, Nnenna G. (PLOS ONE, 2022)
This study empirically examined the impact of external debt on economic growth. Also, the interactions of governance, external debt and external debt volatility were further investigated with emphasize on the interective effect of governance as proxied by Kaufmann, D., (2007) quality governance measures such as; government effectiveness, political stability, voice and accountability, regulatory quality and corruption control on economic growth. The study utilized annual time series data, focusing on thirty selected Sub-Saharan African (SSA) countries for the period 1997 to 2020. The Dynamic System Generalised Method of Moments estimation technique was adopted while controlling for conventional sources of economic growth. Empirical findings from the study reveal that external debt and external debt volatility have a negative and significant impact on economic growth in SSA. Furthermore, the interaction of governance indicators, external debt and its volatility, had a positive impact on economic growth in SSA. This study recommends that SSA government should endeavor to avoid excessive external debt to promote the regions’ capacity to invest in her financial prospects, and to circumvent the danger of repayment of loans using her small income. The SSA governments should also improve the quality of governance by ensuring political stability, minimising corruption, implementing sound policies and regulations that can permit and promote economic growth through the development of the private sector. The governments must ensure that every borrowed debt is properly supervised and utilised for its purposes to spur economic growth. More so, the Guidotti-Greenspan rule of Reserve adequacy should be applied to keep excess borrowings in check.